Garlic peel derived high capacity hierarchical N-doped porous carbon anode for sodium/lithium ion cell. (1st February 2016) - Selvamani, V.; Ravikumar, R.; Suryanarayanan, V.; Velayutham, D.; Gopukumar, S.
Graphical abstract: Nitrogen doped porous carbon nanosheets has been synthesized form cheap as well as easy available precursor (garlic peel) and the electrochemical property towards energy storage has been investigates which, exhibits high reversible capacity, excellent cycling stability and capacity retention during lithium/sodium ion shuttling and may be the possible candidate for high energy application. Highlights: Graphene analogue carbon nanosheets synthesised by cost-effective method. This material exhibited excellent electrochemical performances in Na/Li cells. Pores reduce the ion diffusion path way and easy electrolyte access. The nitrogen present in GPC improves the lithium/sodium ion uptake. In SIB the material delivered 90 mAh g −1 at 1000 mA g −1 with good capacity retention. Abstract: Nitrogen-doped porous carbon synthesised from garlic peel by a simple and cost-effective method has been employed as an anode material for the sodium ion (SIB) as well as lithium ion batteries (LIB). The synthesised material has been found to be mesoporous with a high specific surface area (SSA) ∼1710 m 2  g −1, as calculated with Brunauer–Emmett–Teller (BET) isotherm. Further, Field Emission Scanning Electron Microscopy (FE-SEM) and Transmission Electron Microscopy (TEM) analysis reveal the existence of interconnected micro-pores and voids. The N-doped garlic peel carbon (GPC) exhibits excellent rate capability as well as steady state cycling performance towards sodium and lithium ion shuttlings. Discharge capacities of about 142, 89, 58, 37 mAh g −1 have been achieved at various current densities such as 0.5, 1.0, 2.0, 4.0 A g −1 respectively in a CR-2032 type Na-ion cell. Similarly, the Li-ion cell delivered reversible capacities of about 320, 280, 215 and 145 mAh g −1 at different current densities of 1.0, 2.0, 4.0 and 8.0 A g −1 respectively. The high electrochemical performance of the N-doped GPC is mainly attributed to the existence of nitrogen in the carbon matrix and mesoporous structure coupled with a high surface area for accommodating large number of Li/Na ions.